Allowing privacy-preserving fog computing with digital identity assurance in remote clinical services. (12th January 2023) - Buccafurri, Francesco; Lax, Gianluca; Russo, Antonia
Nowadays, there is an increasing demand for cloud-based remote clinical services, both for diagnosis and monitoring. The COVID-19 pandemic has dramatically amplified this need. E-government programs should quickly go towards the expansion of this type of services, also to avoid that people (especially elderly) renounce treatment or adequate healthcare. However, to be effective, latency between IoT medical devices and the cloud should be reduced as much as possible. For this reason, fog computing appears the best approach, as part of the elaboration is moved closer to the user. However, some privacy threats arise. Indeed, these services can be delivered only based on secure digital identity and authentication systems, but the intermediate fog layer should learn nothing about the identity of users and the link among different service requests. In this paper, we propose a concrete solution to the above issue by leveraging eIDAS-compliant digital identity and by including a cryptographic protocol to provide anonymity and unlinkability of user's access to fog servers.